A de novo germline mutation in MYH7 causes a progressive dominant myopathy in pigs - Murgiano, Leonardo (BioMed Central, 2012)
BACKGROUND: About 9% of the offspring of a clinically healthy Piétrain boar named ‘Campus’ showed a progressive postural tremor called Campus syndrome (CPS). Extensive backcross experiments suggested a dominant mode of inheritance, and the founder boar was believed to be a gonadal mosaic. A genome-scan mapped the disease-causing mutation to an 8 cM region of porcine chromosome 7 containing the MHY7 gene. Human distal myopathy type 1 (MPD1), a disease partially resembling CPS in pigs, has been associated with mutations in the MYH7 gene. RESULTS: The porcine MYH7 gene structure was predicted based on porcine reference genome sequence, porcine mRNA, and in comparison to the human ortholog. The gene structure was highly conserved with the exception of the first exon. Mutation analysis of a contiguous genomic interval of more than 22 kb spanning the complete MYH7 gene revealed an in-frame insertion within exon 30 of MYH7 (c.4320_4321insCCCGCC) which was perfectly associated with the disease phenotype and confirmed the dominant inheritance. The mutation is predicted to insert two amino acids (p.Ala1440_Ala1441insProAla) in a very highly conserved region of the myosin tail. The boar ‘Campus’ was shown to be a germline and somatic mosaic as assessed by the presence of the mutant allele in seven different organs. CONCLUSION: This study illustrates the usefulness of recently established genomic resources in pigs. We have identified a spontaneous mutation in MYH7 as the causative mutation for CPS. This paper describes the first case of a disorder caused by a naturally occurring mutation in the MYH7 gene of a non-human mammalian species. Our study confirms the previous classification as a primary myopathy and provides a defined large animal model for human MPD1. We provide evidence that the CPS mutation occurred during the early development of the boar ‘Campus’. Therefore, this study provides an example of germline mosaicism with an asymptomatic founder.